2018
DOI: 10.1021/acsmedchemlett.8b00050
|View full text |Cite
|
Sign up to set email alerts
|

Stereochemical Structure Activity Relationship Studies (S-SAR) of Tetrahydrolipstatin

Abstract: Tetrahydrolipstatin (THL), its enantiomer, and an additional six diastereomers were evaluated as inhibitors of the hydrolysis of -nitrophenyl butyrate by porcine pancreatic lipase. ICs were found for all eight stereoisomers ranging from a low of 4.0 nM for THL to a high of 930 nM for the diastereomer with the inverted stereocenters at the 2,3,2'-positions. While the enantiomer of THL was also significantly less active (77 nM) the remaining five stereoisomers retained significant inhibitory activities (ICs = 8.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 57 publications
0
14
0
Order By: Relevance
“…We went on to investigate whether a nonadipocyte lipase can cause visceral adipose tissue necrosis and organ failure. For this we first injected pancreatic lipase extracted from pigs (50) into the fat pads of ob/ob mice alone or along with the lipase inhibitor orlistat. Lipase injection dramatically reduced survival over 24 hours (Figure 2A).…”
Section: Introductionmentioning
confidence: 99%
“…We went on to investigate whether a nonadipocyte lipase can cause visceral adipose tissue necrosis and organ failure. For this we first injected pancreatic lipase extracted from pigs (50) into the fat pads of ob/ob mice alone or along with the lipase inhibitor orlistat. Lipase injection dramatically reduced survival over 24 hours (Figure 2A).…”
Section: Introductionmentioning
confidence: 99%
“…In this study, a library of THL stereoderivatives was used to assess the influence of THL stereochemistry on the in vitro inhibition of three essential Mtbencoded lipid esterases/transferases (derivative names given in Figure 1A and full derivative structures given in Figure S1). 14,15 The three lipid esterases included in this study are Antigen 85C (Ag85C), Rv3802, and the thioesterase domain of polyketide synthase 13 (Pks13-TE). All three essential enzymes use a catalytic triad of serine, histidine, and glutamic or aspartic acid, have α/β-hydrolase folds, bind substrates possessing two aliphatic moieties, and have been successfully targeted for drug development.…”
mentioning
confidence: 99%
“…In this study, a library of THL stereoderivatives was used to assess the influence of THL stereochemistry on the in vitro inhibition of three essential Mtb -encoded lipid esterases/transferases (derivative names given in Figure A and full derivative structures given in Figure S1). , …”
mentioning
confidence: 99%
“…Further, each tested compound displayed different potency on each inflammatory factor due to its structural difference, although they all possess same basic skeleton. It indicated that 3D-strcuture is very important in the bioactivity [ 45 , 46 , 47 , 48 , 49 ]. Taken together from PCA, the structural similarity between 2 and 3 is relatively higher than that of the others, and they displayed better effects against IL-1 ß , IL-6 and PGE2 than the others.…”
Section: Resultsmentioning
confidence: 99%